Attribution of poverty among Malaysian students in the United Kingdom - Murnizam Halik; Mohd Dahlan A. Malek; Ferlis Bahari; Norlizah Matshah; Webley, Paul (Universiti Malaysia Sabah, 2012)
This study investigates Malaysian students’ attribution of poverty and attitudes towards the poor in rural Malaysia. A combined total of 124 Malaysian students in the United Kingdom participated in this web-based survey. Factor analysis results reproduce the tripartite (individualistic, structural and fatalistic) structure for attribution of poverty. The results suggest that there is a statistically significant main effect for gender (F3,120=4.48, p=.005) wherein females have a higher attribution for poverty. On attitudes towards the poor, it was found that with upward social mobility, respondents have a more positive attitude towards the poor. It was recommended that further study should focus on how the poor attribute poverty.